PEMETAAN MINAT MATA PELAJARAN GEOGRAFI SEBAGAI MATA PELAJARAN PILIHAN UNBK DI SMAN 2 BATANG ANAI - Naz Maruni; Khairani Khairani (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This study aims to determine: How much interest in geography subjects compared to other UNBK elective subjects of SMAN 2 Batang Anai and what are the basis for students in determining the choice of UNBK elective subjects. This type of research is quantitative descriptive. The study population was all social studies students of class XII IPS, totaling 123 people. Sampling uses the Slovin formula, with the Proportional Random Sampling technique, so that 63 respondents are obtained. Data collection techniques using observation techniques, questionnaire distribution and documentation. Data analysis techniques use percentages. The results showed that: The mapping of interest in geography subjects as UNBK elective subjects at Batang Anai 1 High School based on internal factors was good. This can be seen from the average score obtained 3.76. The mapping of interest in geography as the chosen subject of UNBK in Batang Anai based on external factors is good. This can be seen from the average score obtained 3.65